The influence of social economic business environment on thermography business - Poželaitė, Rūta; Jonuškienė, Erika (Business, Management and Economics Engineering, 2010)
Lithuanian economy survives a recession, business is increasingly difficult to operate in the Lithuanian market. One of the first who suffered the consequences of the economic recession is construction business pushing into difficulties business-related businesses and residents. Due to economic downturn the prices of the construction decreased, consumer spending power diminished, bank lending conditions became tighter, which further undercut the market for construction services. Economic growth has changed the attitude of the population to a warm home, quality of the construction. Although thermography used in the construction industry allows construction companies to ensure their quality of work, people find their homes of poor thermal insulation, moisture retention and more effective to plan for repairs, to check the quality of work carried out by builders and trou-bleshooting to save heat energy and reduce heating costs, but demand for thermography was not great. It is therefore important to find out how the socio-economic environment influences the business of thermography, whether the socio-economic environment al-lows it to develop, or, otherwise, whether it is becoming a threat, reducing the demand for thermography. The aim of this paper is to explore the socio-economic impact on the business environment of thermography business. The methods used in the study were: scientific literature review, secondary data analysis, questionnaire, interview, comparison, clustering methods, PESTLE analysis.The business environment of thermography business can be defined as the business envi-ronment including the global environment and macro environmental factors which affect the entire business, affect success or failure of a business and which the company could not control, and micro-factors that directly affect the company and which the company could influence. The interaction of Lithuanian social and economic environments makes opportunities and threats for thermography business. The poor economic situation influ-ences increasing unemployment, therefore the consumer purchasing power reduces and the incentive to emigrate increases, thus reducing the market of thermography business. As well as the economic situation of the country results in the construction sector in its production decline and increase in bankruptcies of construction companies seeking ways to cost reduction, which reduces the market of thermography business. But the need to save energy, the desire to live in warm housing is still a small possibility of market growth, even in crisis conditions.Article in Lithuanian.Socialinės ekonominės verslo aplinkos įtaka termovizinių tyrimų verslui